Chronic pain and depression in older adult patients treated in outpatient clinics - Ortiz Palomino , Berly (2025)
Chronic pain and depression are prevalent problems in the global geriatric population, with internationally documented bidirectional associations. In Peru, it is estimated that 38.5% of older adults (95% CI: 33.5–44.0) and in Brazil, 47.32%, suffer from chronic pain. The objective of this study was to estimate the association between chronic pain and depression in older adults seen in the outpatient clinic of the San José Police Geriatric Hospital during 2023. This non-experimental, quantitative, analytical, cross-sectional study analyzed 139 older adults (median age 75 years; 61.9% women) from the San José Police Geriatric Hospital during 2023. Standardized questionnaires were administered: the Lattinen Pain Index for chronic pain and the Yesavage GDS-15 for depression. The findings revealed a predominance of severe pain (72.7%), regular analgesic use (73.4%), moderate disability (64.7%), and disrupted sleep (65.5%). Depression was mild in 56.1% and severe in 24.5%. A significant correlation was found between overall chronic pain and depression (p=0.013; ρ=0.209), including intensity (p=0.008; ρ=0.223), frequency (p=0.017; ρ=0.202), disability (p=0.001; ρ=0.274), and hours of sleep (p=0.001; ρ=-0.273). Analgesic use did not show a significant association (p=0.142). The results highlight the need for comprehensive approaches to geriatric pain management that include systematic mood assessment and multimodal intervention strategies.